Changes in quality of life before and after treatment by age in patients with obstructive sleep apnea - Shibano, Akira; Hasukawa, Akihito; Kitahara, Tadashi (Stomato-pharyngology, 2023)
The severity of obstructive sleep apnea （OSA） is not necessarily linked to worsening quality of life （QOL）, and improvement in OSA with treatment does not necessarily mean improvement in QOL. In addition, QOL may differ by age group. The subjects of this study were 34 patients （29 males and 5 females） who underwent bilateral tonsillectomy and soft palate plasty for OSA, and 71 patients （59 males and 12 females） who were treated with nasal continuous positive airway pressure ventilators （nCPAP）. Three months after treatment, changes in quality of life in each treatment group by age group were investigated using the Medical Outcome Study 36-Item Short Form Health Survey （SF-36） version 2 questionnaire. As a result, among patients in their 30s and 40s, the improvement in physical QOL was remarkable in the group treated with surgery, but among those in their 50s, the QOL was better in the CPAP treatment group both physically and mentally. The results indicated that CPAP is not always suitable as a treatment method from the viewpoint of QOL improvement. It is necessary to select a treatment method that takes into account the age group and QOL, and it is also important to evaluate not only whether OSA improves, but also whether QOL improves.